2018
DOI: 10.1016/j.cell.2018.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Heparan Sulfate Organizes Neuronal Synapses through Neurexin Partnerships

Abstract: SummarySynapses are fundamental units of communication in the brain. The prototypical synapse-organizing complex neurexin-neuroligin mediates synapse development and function and is central to a shared genetic risk pathway in autism and schizophrenia. Neurexin’s role in synapse development is thought to be mediated purely by its protein domains, but we reveal a requirement for a rare glycan modification. Mice lacking heparan sulfate (HS) on neurexin-1 show reduced survival, as well as structural and functional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
181
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(192 citation statements)
references
References 72 publications
8
181
3
Order By: Relevance
“…Therefore, it is also possible that Wg and Dlp regulate the starvation-induced synaptic and behavioral plasticities. Furthermore, a recent study revealed that neurexin synaptic organizing proteins are expressed as HSPGs (Zhang et al, 2018). HS modifications in presynaptic neurexins are critical for high-affinity interactions with the postsynaptic ligands neuroligins and the leucine-rich repeat transmembrane neuronal proteins (LRRTMs), and are essential for synapse development at the mouse hippocampus (Zhang et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, it is also possible that Wg and Dlp regulate the starvation-induced synaptic and behavioral plasticities. Furthermore, a recent study revealed that neurexin synaptic organizing proteins are expressed as HSPGs (Zhang et al, 2018). HS modifications in presynaptic neurexins are critical for high-affinity interactions with the postsynaptic ligands neuroligins and the leucine-rich repeat transmembrane neuronal proteins (LRRTMs), and are essential for synapse development at the mouse hippocampus (Zhang et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a recent study revealed that neurexin synaptic organizing proteins are expressed as HSPGs (Zhang et al, 2018). HS modifications in presynaptic neurexins are critical for high-affinity interactions with the postsynaptic ligands neuroligins and the leucine-rich repeat transmembrane neuronal proteins (LRRTMs), and are essential for synapse development at the mouse hippocampus (Zhang et al, 2018). Drosophila Neurexin (Dnrx) is also an HSPG and positively regulates larval locomotion speed and type I bouton growth at NMJs in an HS-dependent manner (Zhang et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also reveal that Neurexin-Robo interaction requires heparin-conjugated moieties and that the synaptogenic activity of Robo is abolished by treatment with heparinase. Since Neurexin1 was recently shown to require a rare glycan modification, heparan sulfate 35 , this posttranslational modification might also participate in increasing the specificity of trans-synaptic interactions between Robo, Slit and Neurexins. Future experiments will need to provide insights into the structure of this and other trans-synaptic protein complex in order to gain further evidence for this coincidence detection model as a mechanism to increase synaptic specificity.…”
Section: Trans-synaptic Coincidence Detection As a Molecular Mechanismentioning
confidence: 99%
“…For example, LRRTMs specifically bind to Nrx (SS4-), Cblns bind to Nrx (SS4+), C1qls bind to Nrx3 (SS5 25b ), dystroglycan bind to Nrx (SS2-and SS4-), and IgSF21 bind to Nrx2a (LNS1) (Sü dhof, 2017; Tanabe et al, 2017;Yuzaki, 2018). Now, Zhang et al, 2018, this issue of Cell provide compelling evidence that Nrxs themselves are heparan sulfate proteoglycans (HSPGs), joining a superfamily of 17 HSPGs (Xu and Esko, 2014). Since HSPGs interact with various HS binding proteins (Condomitti and de Wit, 2018), HS chain-dependent sugar code, in addition to isoform-dependent protein code, likely provide Nrxs with more synaptic binding partners with multifarious functions.…”
mentioning
confidence: 99%